Investigations on Switched Capacitors Based Multilevel Inverters for Grid Connected Photovoltaic Power Generation Systems - Agarwal, Ritika (My University, 2023)
Renewable Energy Systems (RESs) continue to play significantly important role in addressing the concern over global warming. Among various RESs (viz. wind, solar, fuel cells, and hydro), solar energy is being harnessed prominently because it is freely available, there are no moving parts, and can be placed near the load centres. However, the Photovoltaic (PV) based electric power generation is characterized by intermittent output and wide operating range, and therefore requires grid interconnection through power converters or Power Conditioning Unit (PCU). From the viewpoint of easy maintenance and cost-effectiveness, the grid-connected structure can be advantageous for PV systems as they do not use the battery for energy storage. As far as PCU is concerned, the two-stage structure is generally used with PV systems having low and fluctuating output voltage. Such a two-stage structure is usually operated by utilizing a dc-dc converter to regulate the PV output voltage and maximize the output power with voltage boosting feature, and the power conversion process from dc-ac is achieved through an inverter.Traditionally, a two-level inverter is widely used for grid connected systems, but these inverters are characterized by high dv/dt stress, more Electro Magnetic Interference (EMI), and no capability to handle higher voltage range with devices of lower voltage rating. To overcome these issues, Multilevel Inverters (MLIs) have become a preferred choice for low and medium-power dc-ac energy conversion applications to ensure high power quality. Conventional topologies of MLIs pose three major challenges: (a) they require a significantly large number of power devices for an increased number of levels in the output voltage waveform; (b) they required additional circuits and/or complex control methodologies to balance the voltages of the capacitors; and (c) they do not offer any inherent voltage gain, i.e. the voltage is limited to unity. The ongoing research aims to develop new MLIs that offer reduced component count, inherent voltage boosting, simplified voltage balancing, low-Cost Function (CF), suitability for grid connected PV system and easy extension for three phase version. For achieving these features, ‘Switched Capacitors’ based MLIs (SCMLIs) have emerged as suitable candidate.
Keywords: Mutlilevel inverter; Switched Capacitors; Solar PV; Self-boost; Single-phase; Three-phase; Grid connected PV system